Effects of Co-Inoculation of Indole-3-Acetic Acid-Producing and -Degrading Bacterial Endophytes on Plant Growth - Sabitri Adhikari Dhungana; Kazuhito Itoh (Horticulturae, 2019)
Bacterial production of indole-3-acetic acid (IAA) and its effects on plant growth have been frequently studied but there have been few studies on the ecology of IAA-degrading bacteria. In this study, among eight endophytic bacterial strains previously isolated from the same sweet potato sample including two IAA producers, Klebsiella sp. Sal 1 and Enterobacter sp. Sal 3, all of the strains showed IAA-degrading ability to some extent. Herbaspirillum sp. Sal 6 had the highest activity for IAA and tryptophan. When the IAA producers and the degrader were co-cultured in tryptophan-amended N+MR liquid medium, the concentrations of IAA decreased. Inoculation with Klebsiella sp. Sal 1, the highest IAA producer among the test strains, increased fresh root weight of tomato and radish, but the effect decreased by co-inoculation with IAA-degrading Herbaspirillum sp. Sal 6. Since both strains colonized plant parts at high populations, it was likely that the IAA degrader decreased IAA levels in the plants by degrading IAA and/or its precursor tryptophan. When IAA-producing biofertilizers are used, interactions with IAA degraders in plants should be considered.